Diverse binding modes, same goal: The receptor recognition mechanism of botulinum neurotoxin. Issue 2 (March 2015) - Lam, Kwok-Ho; Yao, Guorui; Jin, Rongsheng
Abstract: Botulinum neurotoxins (BoNTs) are among the most deadly toxins known. They act rapidly in a highly specific manner to block neurotransmitter release by cleaving the soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) complex at neuromuscular junctions. The extreme toxicity of BoNTs relies predominantly on their neurotropism that is accomplished by recognition of two host receptors, a polysialo-ganglioside and in the majority of cases a synaptic vesicle protein, through their receptor-binding domains. Two proteins, synaptotagmin and synaptic vesicle glycoprotein 2, have been identified as the receptors for various serotypes of BoNTs. Here, we review recent breakthroughs in the structural studies of BoNT–protein receptor recognitions that highlight a range of diverse mechanisms by which BoNTs manipulate host neuronal proteins for highly specific uptake at neuromuscular junctions.